Transgovernance: Advancing sustainability governance - Louis Meuleman (Springer, 2013)
Transgovernance: Advancing Sustainability Governance analyses the question what recent and ongoing changes in the relations between politics, science and media - together characterized as the emergence of a knowledge democracy - may imply for governance for sustainable development, on global and other levels of societal decision making, and the other way around: How can the discussion on sustainable development contribute to a knowledge democracy? How can concepts such as second modernity, reflexivity, configuration theory, (meta)governance theory and cultural theory contribute to a "transgovernance" approach which goes beyond mainstream sustainability governance? This volume presents contributions from various angles: international relations, governance and metagovernance theory, (environmental) economicsand innovation science. It offers challenging insights regarding institutions andtransformation processes, and on the paradigms behind contemporary sustainability governance. This book gives the sustainability governance debate a new context. It transforms classical questions into new options for societal decision making and identifies starting points and strategies towards effective governance of transitions to sustainability.
Keywords: 330; Political Science; general; Social Policy; Business Ethics; Non-Profit Enterprises/Corporate Social Responsibility; Sustainable Development